Avaliação de diferentes processos de extração de α e β ácidos do lúpulo aplicáveis em alimentos - Moraes, Juliana Federsom de (Universidade Federal de São Carlos, 2025)
Natural antimicrobials are necessary as substitutes for synthetic ones due to consumer market demands for clean-label foods. Over time, dietary consumption patterns have adjusted, with consumers seeking foods that contain natural or organic ingredients or those with reduced amounts of components perceived as harmful to health. The aim of this study was to develop an extraction method to obtain α-acids and β-acids from hops, aiming at antimicrobial applications in food. Hops were subjected to two extraction methods—agitation and ultrasound assisted extraction—using three different types of plant-based oils (sunflower oil, soybean oil, and olive oil). In addition to the type of solvent, the extraction parameters evaluated included temperature (20–60 °C) and the ratio of solvent mass to sample mass (1/10–30 g/mL). The raw material was characterized in terms of moisture content and composition of α-acids and β-acids. The extraction performance was evaluated based on yield and recovery of α-acids and β-acids using spectrophotometric techniques. The best extraction performance was achieved through agitation using soybean oil at room temperature (20 °C) and a solute-to-solvent ratio of 1/20 (g/mL). For ultrasound-assisted extraction, a power of 280 W and an extraction time of 6 minutes were determined to be the conditions yielding the highest extraction efficiency and recovery. The extracts obtained under optimal conditions were further characterized in terms of rheological properties and acidity. Therefore, this study evaluated multiple variables in both agitation and ultrasound-assisted extraction methods, enabling the selection of ideal parameters for the future application of the extracted antimicrobials in food products.
Evaluation of different extraction processes of α and β acids from hops applicable to food
Keywords: Bioativos; Ultrassom; α-ácidos; ꞵ-ácidos; Humulus lupulus; Pellets; Bioactives; Bioactives; Ultrasound; α-acids; β-acids; Solid - liquid extraction; CIENCIAS AGRARIAS::CIENCIA E TECNOLOGIA DE ALIMENTOS::CIENCIA DE ALIMENTOS::QUIMICA, FISICA, FISICO-QUIMICA E BIOQUIMICA DOS ALIM. E DAS MAT.-PRIMAS ALIMENTARES; 3. Saúde e Bem-Estar; 9. Indústria, Inovação e Infraestrutura